Constitutional Revolution in Naples 1820—1821 in Сoverage of Russian Press - O. V. Anisimov (Научный диалог)
The article deals with the reaction of the Russian press to the revolutionary events in Southern Italy in 1820—1821. The main sources were the journals “Vestnik Evropy”, “Nevsky Spectator”, “Son of the Fatherland”, and the official newspaper “St. Petersburg Vedomosti”, and the foreign press was also involved. In the course of the study, the main methods of conveying information to the reading public in Russia on such issues as the development of the revolutionary process in Naples, the reaction of the powers of the Holy Alliance, the role of the Carbonari society and the significance of the separatist movement in Sicily were established. It was possible to correct the conclusions of scientists of the USSR regarding the presentation of the news agenda in journals close to the Decembrist circles. The novelty of the study is seen in the fact that the prevailing influence of the Austrian press on the Russian press was established; the latter imported views on the constitutional process in Naples as the result of a conspiracy by the “sect” of the Carbonari. Materials were established that stood out from the prevailing agenda and considered the events of the Neapolitan Revolution of 1820 from the point of view of political economy.